Lince Platform: social innovation for refugees, immigrants and stateless people - Madeira, Thaíse Valentim (2022)
The number of people forced to move around the world has increased significantly in the last 20 years. Considering this scenario, the Lince Platform, a result of the Technological Innovation Program, was created to support a database for the reception, legal assistance and social inclusion of refugees, immigrants and stateless persons in Brazil. For this purpose, this study first collected data on the most evidente needs and demands of the platform’s target audience by means of bibliographic and documentary research, besides fieldwork on migrants’ experience reports and interviews with public and private agencies. In the virtual space of the Lince Platform, of collective use, members may work collaboratively, experimenting with forms of sociability and collectively proposing discussions, projects and other forms of mobilization and social interaction. It is expected thus that the platform may, in the short, medium and long term, serve as a starting point for developing proposals that engage refugees, immigrants, and stateless persons in participatory diagnostic activities and in the planning of democratic public policies, considering how they appropriate the new territory in which they are inserted.